The effect of different flow levels and concentrations of sevoflurane during the wash-in phase on volatile agent consumption: a randomized controlled trial - SARAÇOĞLU, AYTEN (My University, 2022)
Purpose The standard procedure for low-flow anesthesia usually incorporates a high fresh gas flow (FGF) of 4-6 L/minute during the wash-in phase. However, the administration of a high FGF (4-6 L/min) increases the inhaled anesthetic agent consumption. This study was designed to compare the sevoflurane consumption at 2 rates of flow and vaporizer concentration during the wash-in period. Methods Patients were randomly enrolled into high FGF (HFGF) (n = 30) and low FGF (LFGF) (n = 30) groups. During the wash-in, the HFGF group received 4 L/minute FGF with a sevoflurane vaporizer setting of 2.5%, and the LFGF group received 1 L/minute FGF with a vaporizer setting of 8%. Once the wash-in was complete, anesthesia maintenance was performed with 0.5 L/min FGF with a vaporizer setting of 2.5-4.5% in both groups. The patient demographic data, bispectral index values, hemodynamic variables, wash-in time, sevoflurane consumption during the wash-in phase, and total sevoflurane consumption were analyzed. Results The median sevoflurane consumption in the wash-in phase was 8.2 mL (7.1-9.3) in the HFGF group and 2.7 mL (2.2-3.1) in the LFGF group (p = 0.001). The mean total sevoflurane consumption was 17.41 +/- 3.58 mL in the patients who received HFGF and 14.93 +/- 3.57 mL in the LFGF group (p = 0.001). The mean wash-in completion time was 12.49 +/- 2.79 min in the HFGF group and 3.35 +/- 0.67 min in the LFGF group (p = 0.001). Conclusions The anesthetic agent consumption during the wash-in phase was approximately 3 times lower with the administration of sevoflurane at 1 L/minute FGF than the use of 4 L/minute FGF.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Anesteziyoloji; Medicine; Health Sciences; Surgery Medicine Sciences; Anesthesiology; ANESTEZİYOLOJİ; Klinik Tıp; Klinik Tıp (MED); ANESTHESIOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Anesteziyoloji ve Ağrı Tıbbı; Anesthesiology and Pain Medicine; Anesthesia; Anesthetic agent consumption; Low-flow anesthesia; Sevoflurane; Wash-in; ANESTHESIA; DESFLURANE; Anesthesia; Anesthetic agent consumption; Low-fow anesthesia; Sevofurane; Wash-in